Biorenewable resources : engineering new products from agricultures - Brown, Robert Clinton, 1954- (Ames : Blackwell, 2003)
Immense potential for sustainable development lies in the production of fuels, chemicals, and materials from bioresources. This timely book provides comprehensive coverage of the engineering systems that convert agricultural crops and residues into bioenergy and biobased products. Leading the way as the first textbook for coursework on biobased products, Biorenewable Resources: Engineering New Products from Agriculture covers not only pertinent technologies but offers a primer on necessary foundation subjects the student or other reader may lack: organic chemistry, thermodynamics, plant science, crop production, environmental science, and process economics. Of special value to those working or planning to work in the field are compilations of bioresource properties, such as production yields, bulk densities and moisture content, summative analysis of plant materials, and chemical conversion yields. By defining this multi-disciplinary field-at the interface between agricultural sciences and process engineering-Robert C. Brown has produced an introductory textbook that also serves as a handbook for agronomists, engineers, chemists, and environmentalists.